Технологічні принципи моделювання харчової продукції з підвищеним умістом біологічно активних речовин - Силка, Ірина Миколаївна; Sylka, Iryna; Ющенко, Наталія Михайлівна; Yushchenko, Nataliia; Фролова, Н. Е.; Frolova, N.; Попик, О. О.; Popyk, O. (Запоріжжя: ТДАТУ, 2025)
UA: У статті розкрито питання розширення асортименту солодких страв за рахунок уведення нових рецептурних компонентів із метою задоволення смакових уподобань споживачів та зростаючого попиту на оздоровчі харчові продукти у закладах ресторанного господарства. Установлено, що піноутворююча здатність рецептурних композицій зростає за збільшення пюре айви і досягає 280% за тривалості збивання від 12 до 16 хв для зразка з рівними масовими співвідношенням пюре айви та яблук. Проведено повну заміну желатину на метилцелюлозу, що покращує органолептичні показни-ки і розширює коло споживачів, а саме веганів. Розроблена страва «Самбук айвово-яблучний» має низьку калорійність (126 ккал) та підвищений (у 1,5 рази) уміст пектину, що становить 45% від рекомендованої денної норми.Упровадження розробленої страви до меню закладів ресторанного господарства є доцільним з огляду на високу органолептичну оцінку, низьку енергетичну цінність та підвищений уміст біологічно активних речовин, зокрема пектину. /// EN: The article discusses the issue of expanding the range of sweet dishes by introducing new recipe components in order to satisfy consumer taste preferences and the growing demand for healthy food products in restaurants.Apple sambuk is a classic sweet dish in Ukrainian cuisine. The developed recipe replaces gelatin as a gelling agent with the food additive methylcellulose, which improves the organoleptic characteristics and broadens the consumer base, particularly among vegans.It was found that the foaming ability of the formulations increases with the addition of quince puree. This indicator reaches 280% with a whipping duration of 12 to 16 minutes for a sample with equal mass ratios of quince puree and apple puree.Quince puree contains more structure-forming substances, which accelerates the solidification of the recipe formulation. The sample based on quince puree with methylcellulose solidifies within 45 minutes and is ready for consumption, unlike the control sample based on applesauce and gelatin, which requires 85 minutes.However, increasing the quince content beyond 50% leads to reduced uniformity, increased density and heterogeneity of the finished product, as well as a deterioration in organoleptic qualities: the delicate, pronounced taste and aroma become sharper with the characteristic tartness of quince.The developed dish «Quince-Apple Sambuk» has a low energy value of 126 kcal and a 1.5-fold higher pectin content, which constitutes 45% of the recommended daily allowance.The introduction of this dish into restaurant menus is advisable, given its high organoleptic evaluation, low energy value, and high content of biologically active substances, in particular pectin.
Technological principles of modeling food products with an increased content of biologically active substances
Keywords: харчові продукти; біологічно активні речовини; солодкі страви; ресторанне господарство; оздоровчі властивості; харчові добавки; веганство; functional food products; biologically active substances; sweet dishes; restaurant industry; nutritional properties; food additives; vegan diets